Laku Tasawuf sebagai Terapi Psikospiritual - Dikhorir Afnan (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2018)
ABSTRACT Human existence is built on the consciousness of two things as transcendent creatures (transcendere), and as immanent beings (Latin: immanere, abiding within). Man makes himself, with all activities and the result builds his own uniqueness (Syam, 2015). One of the traditions and culture of Javanese society in the spiritual context is the behavior of Sufism. The research was conducted to trace the ritual of worship as transedental creature in group of jamaah